Metastable ferroelectric phase and crossover in the Ba2NdFeNb4−xTaxO15 TTB solid solution12. Issue 6 (26th January 2018) - Albino, M.; Heijboer, P.; Porcher, F.; Decourt, R.; Veber, P.; Maglione, M.; Josse, M.
Abstract : Insightful chemical, structural and dielectric characterizations reveal a metastable ferroelectric phase and crossover in Ba2 NdFeNb4− x Ta x O15 TTB. Abstract : In the framework of the crystal chemical investigation of Tetragonal Tungsten Bronze (TTB) niobates, the Ba2 NdFeNb4− x Ta x O15 solid solution has been investigated in order to gain insights on the relaxor to ferroelectric crossover and its features. Single-phase ceramics were synthesised by conventional two-step firing and sintering and they underwent extended chemical, structural, microstructural and physical characterizations. For Nb-rich compositions ( x ≤ 0.5), the temperature dependence of the dielectric permittivity, the pyroelectric coefficient, and also the ferroelectric hysteresis loops revealed a nonconventional relaxor to ferroelectric crossover, which was confirmed by piezoelectric measurements for x ≤ 0.1. A thermal hysteresis of the ferroelectric transition revealed the existence of a metastable ferroelectric phase in these TTB niobates. An accurate and reliable dielectric phase diagram is established from these observations, which allows discussing the original sequence of dielectric phase transitions encountered in this solid solution.